Transcriptomic and gene-family dynamic analyses reveal gene expression pattern and evolution in toxin-producing tissues of Asiatic toad (Bufo gargarizans) - Lv, Yunyun; Li, Yanping; Wen, Zhengyong; Shi, Qiong (Frontiers in Ecology and Evolution, 2022)
Comprising a major clade of Anura, toads produce and secrete numerous toxins from both the parotoid glands behind their eyes and their dorsal skin. These toxins, made of various proteins and compounds, possess pharmacological potential to be repurposed to benefit human health. However, the detailed genetic regulation of toad toxin production is still poorly understood. A recent publication uncovering the genome of the representative Asiatic toad (Bufo gargarizans) provides a good reference to resolve this issue. In the present study, we sequenced the transcriptomes of parotoid gland, dorsal skin and liver from the Asiatic toad. Combining our data with 35 previously published transcriptomes across eight different tissues from the same species but from different locations, we constructed a comprehensive gene co-expression network of the Asiatic toad with the assistance of the reference genome assembly. We identified 2,701 co-expressed genes in the toxin-producing tissues (including parotoid gland and dorsal skin). By comparative genomic analysis, we identified 599 expanded gene families with 2,720 genes. Through overlapping these co-expressed genes in the toad toxin-producing tissues, we observed that three cytochrome P450 (Cyp) family members (Cyp27a1, Cyp2c29, and Cyp2c39) were significantly enriched in pathways related to cholesterol metabolism. Specifically, 3-hydroxy-methylglutaryl CoA reductase (hmgcr), encoding the major rate-limiting enzyme, appears with multiple copies in both Asiatic toad and common toad, possibly originating from a tandem duplication event. The five copies of hmgcr genes consistently displayed higher transcription levels in the parotoid gland when compared with the abdominal skin, suggesting it as a vital candidate gene in the involvement of toad toxin production. Taken together, our current study uncovers transcriptomic and gene-family dynamic evidence to reveal the vital role of both expanded gene copies and gene expression changes for production of toad toxins.